Empowerment of Women's Leadership Through Various Technical and Vocational Education and Training (TVET) Programmes - Des Iskandar Ismail,; Ab Halim, Fazlinda (Journal of TVET and Technology Review, 2023)
This systematic literature review identifies women's leadership empowerment through various Technical and Vocational Education and Training (TVET) programmes. Women in leadership positions offer numerous advantages and play a crucial role in achieving gender equality and fostering a more inclusive and prosperous society. 20 articles based on qualitative and quantitative research from prominent research platforms such as Scopus, Directory of Open Access Journal (DOAJ), and Google Scholar were analysed using PRISMA guidelines. The review determines nine training programme domains and their impact on the development of women's leadership, such as Change Management, Coaching and Mentoring, Conflict Resolution, Communication Skills, Gender Equality, Inspiring workers, Leading Innovation, Problem-solving, and Project Management. The findings reveal the significance of implementing and expanding specialised TVET programmes to ensure women's active participation and leadership in various sectors. This study highlights the transformative potential of TVET in empowering women and calls for further research and policy development in this field.